Mission Impossible? Preventing discrimination on grounds of disability of foetuses with Down syndrome in Spain after the emergence of non-invasive prenatal testing. Issue 3 (September 2019) - Rodríguez Díaz, Begoña
This article analyses the current situation of discrimination towards foetuses with Down syndrome (DS) in Spain, both legally and through the medical practice, pointing out how this discrimination breaches the United Nations Convention on the Rights of Persons with Disabilities (CRPD), ratified by Spain, according to the Committee of the CRPD. This work argues that an eventual modification of the Spanish abortion legislation (in appeal before the Constitutional Court) might not be enough to prevent the said discrimination due to the emergence of the non-invasive prenatal testing (NIPT). It explores the challenges introduced by the NIPT and the relationship between a prenatal diagnose of a disability (DS in particular) and termination of pregnancy rates. Health practitioners, mainly through the communication of the diagnose, play a significant role in the bias against the DS population that leads to discrimination. Consequently, this article suggests the need for a different approach towards a DS diagnose, more accurate, positive and based on the actual experience of individuals with DS and their families.